Airway and esophageal eosinophils in children with severe uncontrolled asthma. Issue 12 (23rd October 2018) - Erkman, Jessica; Vaynblat, Allen; Thomas, Kristen; Segal, Leopoldo N.; Levine, Jeremiah; Moy, Libia; Greifer, Melanie; Giusti, Robert; Shah, Rasik; Kazachkov, Mikhail
Abstract: Aim: Children with severe uncontrolled asthma (SUA) have a high burden of symptoms and increased frequency of asthma exacerbations. Reflux esophagitis and eosinophilic esophagitis are important co‐morbid factors for SUA. Both are associated with the presence of eosinophils in esophageal mucosa. We hypothesized that esophageal eosinophils are frequently present and correlate with the presence of airway eosinophils in children with SUA. Method: We performed a retrospective analysis of a prospective database of children who underwent "triple endoscopy" (sleep laryngoscopy, bronchoscopy with bronchoalveolar lavage [BAL] and endobronchial biopsy [EBB], and esophagogastroduodenoscopy with esophageal biopsy [EsB]) at our Aerodigestive Center for evaluation of SUA. Children with known cystic fibrosis, primary ciliary dyskinesia, and aspiration‐related lung disease were excluded. Result: Twenty‐four children (21 males) ages 2‐16 years were studied. Elevated BAL eosinophils were found in 10 (42%) patients, endobronchial eosinophils in 16 (67%); 7 (29%) had endobronchial eosinophils without elevated BAL eosinophils. Esophageal eosinophils were found in 11 (46%) patients. There was a correlation between the amount of eosinophils in BAL and EBB ( R = 0.43, P = 0.05) airway eosinophils, defined as elevated BAL and/or EBB eosinophils, correlated with esophageal eosinophils ( R = 0.41, P = 0.047). Conclusion: We concluded that airway and esophageal eosinophils are frequently present in children with SUA.